Comparing Faithfully: Insights for Systematic Theological Reflection - Michelle, Voss Roberts (Comparative Theology: Thinking Across Traditions (FUP), 2016)
In comparative theology, an adherent of one religious tradition reflects on faith through deep and focused conversation with another tradition. This volume equips students of Christian theology for leadership in a pluralistic world through conversations about God, theodicy, humanity, Christology, and soteriology that take seriously the wisdom of religious neighbors